2020
DOI: 10.1371/journal.pone.0228852
|View full text |Cite
|
Sign up to set email alerts
|

Intake frequency of vegetables or seafoods negatively correlates with disease activity of rheumatoid arthritis

Abstract: Objective To clarify the relationship between dietary habit and disease activity of rheumatoid arthritis (RA). Methods This study enrolled RA patients who met the ACR/EULAR 2010 classification criteria from Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) cohort in 2015. 22item food frequency questionnaire (FFQ) was taken for the measurement of dietary habit in a single-institution cohort of RA (Kyoto University Rheumatoid Arthritis Management Alliance: KURAMA) in 2015. The disease activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Dietary habits of RA patients were obtained from the self-reported questionnaire as described previously 14 , 18 . This questionnaire consisted of 20 items about the intake frequency of 1. staple food (rice, bread or noodles) for breakfast, 2. staple food for lunch, 3. staple food for dinner, 4. meat, 5. fish, 6. tofu (soybean curd), 7. eggs, 8. milk, 9. vegetables, 10. fruits, 11. deep-fried foods, 12. cakes, 13. juice or isotonic drinks, 14. junk foods, 15. sweets like candies and chocolates, 16. frozen foods, 17. pickles, 18. ham, sausage or kamaboko (boiled fish paste), 19. miso soup (fermented soybean paste) and by the participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary habits of RA patients were obtained from the self-reported questionnaire as described previously 14 , 18 . This questionnaire consisted of 20 items about the intake frequency of 1. staple food (rice, bread or noodles) for breakfast, 2. staple food for lunch, 3. staple food for dinner, 4. meat, 5. fish, 6. tofu (soybean curd), 7. eggs, 8. milk, 9. vegetables, 10. fruits, 11. deep-fried foods, 12. cakes, 13. juice or isotonic drinks, 14. junk foods, 15. sweets like candies and chocolates, 16. frozen foods, 17. pickles, 18. ham, sausage or kamaboko (boiled fish paste), 19. miso soup (fermented soybean paste) and by the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Nutritional interventions such as protein supplementation were found to improve physical function of the frail elderly in several clinical trials 13 . In the RA population, seafood, fruits and vegetables have beneficial effects on disease activity 14 , whereas high-fat diets have the opposite effect by leading to a pro-inflammatory response 15 . Even though several nutrients are expected to have therapeutic effects both on frailty and inflammatory diseases, clinical correlations between dietary habits and frailty with RA have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a pilot study has shown that potassium supplementation improves joint pain in RA patients with hypokalemia [37]. Moreover, our group has previously reported that potassium-rich ingredients such as fruits and vegetables are signi cantly associated with lower RA disease activity [38]. In summary, the urinary Na/K ratio is an independent disease activity marker of RA, and increased Na intake and decreased K intake may contribute to RA pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…The analyses in the current study were conducted using the Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) cohort database, with approval from the ethics committee of Kyoto University Hospital. The KURAMA cohort was established in May 2011 at the Center for Rheumatic Disease at Kyoto University Hospital with the aims of providing strict control of RA and using patient clinical and laboratory data for clinical investigations [11][12][13]. Clinical, biological and functional data were recorded at baseline and every visit.…”
Section: Patientsmentioning
confidence: 99%